Learning from the Origins - Alexander Yarkin (Center for Economic Studies and ifo Institute (CESifo), 2023)
How do political preferences and voting behaviors respond to information coming from abroad? Focusing on the international migration network, I document that opinion changes at the origins spill over to 1st- and 2nd-generation immigrants abroad. Local diasporas, social media, and family ties to the origins facilitate the transmission, while social integration at destination weakens it. Using the variation in the magnitude, timing, and type of origin-country exposure to the European Refugee Crisis of 2015, I show that salient events trigger learning from the origins. Welcoming asylum policies at the origins decrease opposition to non-Europeans and far-right voting abroad. Transitory refugee flows through the origins send abroad the backlash. Data from Google Trends and Facebook suggests elevated attention to events at the origins and communication with like-minded groups as mechanisms. Similar spillovers following the passage of same-sex marriage laws show the phenomenon generalizes beyond refugee attitudes.
Keywords: O15; Z13; D72; D83; P00; J61; F22; 330; immigration; social networks; spillovers; political attitudes; integration